The role of Gadolinia Doped Ceria support on the promotion of CO2 methanation over Ni and NiFe catalysts. (26th October 2017) - Frontera, P.; Macario, A.; Monforte, G.; Bonura, G.; Ferraro, M.; Dispenza, G.; Antonucci, V.; Aricò, A.S.; Antonucci, P.L.
Abstract: In the present work, CO2 methanation was investigated over Ni, Fe, Ni3 Fe1, Ni1 Fe1 and Ni1 Fe3 catalysts supported on Gadolinia Doped Ceria (GDC) in the temperature range 200–400 °C. Both CO2 and H2 conversion decreased in the order Ni/GDC > Ni3 Fe1 /GDC > Ni1 Fe1 /GDC > Ni1 Fe3 /GDC. No catalytic activity was displayed by Fe/GDC. Maximum CO2 conversion (>90%) was observed at 400 °C, with almost 100% selectivity to CH4 . The catalysts were characterized by X Ray Diffraction (XRD), N2 adsorption/desorption, H2 – Temperature Programmed Reduction (H2 -TPR), Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS) and CO2 Temperature Programmed Desorption (CO2 -TPD). The superior activity of monometallic Ni/GDC with respect to bimetallic NiFe/GDC catalysts was ascribed to the presence of surface oxygen vacancies induced by the GDC support, an enhanced basicity of the Ni-rich samples, as well as to the ability of the Ni-GDC to interact with CO2, as suggested by XPS data. Highlights: The role of Gadolinia doped Ceria support of bimetallic catalyst Ni/Fe have been investigated. The obtained results showed a superior catalytic activity of the monometallic catalyst whit respect to the bi-metallic ones. The support play a decisive role in the metal-support interaction.